Kamban’s New Creative Strategy and Iraniyan’s Story - K, Murugesan (Indian Journal of Tamil, 2023)
The Kamba Ramayanam is a unique cultural repository of Tamil society, a treasure of the arts, and an epic in which the Supreme God has incarnated in this soil, bearing a human form. The learners will be well aware of the poetic ability of Kambar, who flavoured the fruits that had been soaked in the heart of Valmiki, the primordial poet, and who then amplified the taste of that fruit. In more than 10,000 of the six chapters, Kambar, who records the divinity of Rama and the greatness of his human birth, brings through it many sub-stories, introduces them, and gives a flavour to the epic. In this way, this article examines the necessity of the Iraniyan story in the Yuddha Kandam (Chapter on War), the creative strategy of the epic scholar to include this subplot in between, and the reason for this.